Developing a Strategic Program for Chilean Health Information Technology Environmental Scan and Key Informant Interviews - Taylor, Erin Audrey (RAND Corporation, 2016)
As part of an effort to assist Chile in developing a strategic program to foster the development of the health information technology (health IT) sector over the next five to ten years, this report assesses the current state of health IT adoption and implementation in Chile, as well as the challenges and opportunities facing the sector over the coming years.